The Influence of Spraying on Argentine (Iridomyrmex humilis) and Native Ants (Hymenoptera Formicidae) - Majer, Jonathan; Flugge, R. (1984)
Experiments and observations on the ecology of the Argentine ant (Iridomyrmex humilis) and the effect of heptachlor spraying on this, and native ant species were performed over a 1 year period.The aim was to :-a) Investigate the distribution pattern of the Argentine ant and to relate this to that of sympatric native ants, andb) To investigate the immediate effect of spraying on Argentine and native ants and to follow the subsequent recovery in ant fauna over a 1 year period. The ant was observed colonizing large contiguous tracts of land.It exhibited a summer foraging peak but activity decreased greatly and distribution became more localised during winter. Only eight species of native ants were found in the Iridomyrmex humilis dominated plot which was studied (low species richness) and most ants sampled were Iridomyrmex humilis (low species evenness). Some native ant species in the plot occurred in gaps in the Argentine ants1 distribution, others were distributed independently of this ant and Adlerzia froggatti was positively associated with Iridomyrmex humilis.Jet spraying of 0.5% heptachlor totally eradicated Iridomyrmex humilis and two other species of ants i n one plot. Iridomyrmex humilis had not returned by the final survey date,almost 1 year later. Its range had largely been replaced by the meat ant, Iridomyrmex purpureus. As a result of this finding, some possible methods of limiting Iridomyrmex humilis by replacing it with native ants are suggested.